Petrological evolution of the Middle Triassic Predazzo Intrusive Complex, Italian Alps. Issue 8 (11th June 2018) - Casetta, Federico; Coltorti, Massimo; Marrocchino, Elena
ABSTRACT: The Predazzo Intrusive Complex (PIC), a Ladinian plutonic body located in the Southern Alps (NE Italy), is made up of a 4.5 km 3 gabbroic to syenitic and syenogranitic intrusion, basaltic to latitic volcanic products (about 6 km 3 in volume) and by an extended dike swarm intruding both intrusive and volcanic rocks. An extensive field survey of the complex, followed by detailed petrographic and geochemical analyses, allowed the identification of three different magmatic units: a Shoshonitic Silica Saturated Unit (SS), 3.1 km 3 in volume, a Shoshonitic Silica Undersaturated Unit (SU), 0.3 km 3 in volume, and a Granitic Unit (GU), 1.1 km 3 in volume. K-affinity, marked Nb and Ti negative anomalies and a strong Pb enrichment are distinctive markers for all PIC lithotypes. A general HFSE (Th, U, Pb), LREE (La, Ce, Pr, Nd) and Na enrichment characterizes the SU suite with respect to the SS series. Mass balance calculations, based on major and trace element whole rock and mineral compositions, have been used to simulate the fractionation process of SS and SU suites, showing (i) the complexity of the evolutionary stages of the PIC and (ii) the analogy between the calculated subtracted solid assemblages and the natural cumulitic lithotypes outcropping in the area. The field relationships between the various portions of the intrusive complex, the volcanic products and the dike swarm define the temporal evolution of the PIC, in which the SS magma batch was followed by the GU and later on by the SU intrusion. The presence, in both eastern and western portions of the complex, of a transitional magmatic contact between the intrusive rocks of the SS suite and the volcanics is not in favour of the hypothesis of a caldera collapse to explain the ring-like shape of the PIC.